The Lower Krishna Basin: basin closure and shifting waterscape in South India - Venot, Jean-Philippe; Turral, Hugh; Samad, Madar (2007)
Since the 1850s, the Krishna basin has seen an increasing mobilization of its water resources and a dramatic development of irrigation, with little regard to the limits of available water resources. This progressively led to the closure of the basin: surface water resources are now almost entirely committed to human consumptive uses; the increasing groundwater abstraction negatively affects the surface water balance by decreasing base flows, and the discharge to the ocean continues to decrease. The lower Krishna basin, located in Andhra Pradesh, is a deficit sub-basin; it depends highly on inflow from the upper basin and on upstream water uses. It is the first part of the Krishna basin to face the adverse consequences of any hydrological changes. It is also the region of the basin where most of the available water is depleted by human consumptive uses. In times of drought, it is the first region to face severe water shortages and to witness a spatial re-distribution or re-appropriation of water. Taking place on the basis of current political, institutional and geographical forces, this re-appropriation of water raises socio-political questions of sectoral and regional water apportionment within the lower Krishna basin and may be at the origin of conflicts between water users. This paper identifies two main drivers to the lower Krishna basin closure: (i) a long-term trend towards decreasing water availability with a declining surface water inflow due to water development in the upper basin and (ii) a local water over-commitment due to uncontrolled development of private groundwater abstraction and short term management decisions, both at the farmer and command area levels, in the large irrigation projects of the lower Krishna basin. In 1996/2000, 80% of the lower Krishna basin net inflow was depleted and discharge to the ocean amounted to 17.9 km3/yr, defining a moderately modified ecosystem. During the drought of 2001/2004, likely to forecast the future waterscape of the lower Krishna basin, all indicators point to further water resource commitment with a depleted fraction amounting to 98% of the net inflow, a lack of discharge to the ocean and the shrinkage of surface irrigated agriculture. This paper illustrates that local users and managers participate to a large extent in the shifting waterscape of the lower Krishna basin. At the basin scale, this paper shows that both the intra-agriculture and the inter- sectoral distribution of water are being reshaped. In the agricultural sector, the strong political divide among the three regions of Andhra Pradesh and the need to balance rural development among those regions are two of the main driving forces of a shifting agricultural water use. If surface water distribution among large irrigation projects tends to be to the advantage of the politically influent coastal region; the uncontrolled groundwater development mainly benefits the dry upland regions of Telangana and Rayalaseema and is tantamount to a spatial and social redistribution of water impinging surface water use in the lower reaches of the basin. The inter-sectoral distribution of water is also being modified. First, increasing power needs have led to the completion of hydro-power projects which do not yet impact other uses. Second, domestic and industrial needs of urban areas are increasing and are preferentially met. Currently, this is not affecting existing water uses as volumes considered remain marginal but in case of drought it could further deprive agricultural uses in the large irrigation projects located downstream. Third, environmental degradation has led to increasing awareness to recognize the environment as a water user in its own right. This has yet to be translated in formal allocation mechanisms and will point to further water commitment letting very little room for further water resources development. At the local level, this study highlighted a large range of adaptive strategies developed by both farmers and managers in the large irrigation projects of the lower Krishna basin. Strategies include: differential canal supply management, reduction of the cropping season, crops shift, development of groundwater use, etc. Strategies vary both temporally and spatially and reflect the particular political economy of the region studied To overcome the degradation of the resource base and the management difficulties linked to resource over- commitment, this paper underlines that the state has to play a central role in articulating a specific course among different available options through the definition and the implementation of formal effective and adaptive water allocation mechanisms, both in time and space, to allow transparent and sustainable use of available water resources. At present, calls for demand management by the State and international donors are strong but the consideration and implementation of mega inter-basin transfers perpetuates an unsustainable rush towards further resource mobilization and should not be taken as a justification for disregarding other management options that will allow regulating water use notably in the agricultural sector. Finally policies limited to the water sector are unlikely to ease the pressure on the water resources and there is a clear need for strategies and policies that would ensure the rural population to make a successful transition beyond agriculture.